I love you - McBride, Martina; Worley, Paul; Follese, Adrienne; Follese, Keith; Sony Music (New York : Sony Music, 1999)
Contains the single taken from the soundtrack album Runaway Bride (Julia Roberts, Richard Gere)-Music From The Motion Picture.
I Love You (2:54)
Koleksi Khas Wiramanja.
Title from disc label.
Keywords: Film soundtracks; Motion pictures and music